Basic Principles of Leading Methods in Translating Folklore Works - Fayzulloev O.M.; Muxamadova A.O. (Universitas Muhammadiyah Sidoarjo, 2022)
The article discusses basic principles of leading methods in translating folklore works and takes into consideration various methods of translating of literary texts.